PISA and its consequences: Shaping education policies through international comparisons - Niemann, Dennis; Martens, Kerstin; Teltemann, Janna (European Journal of Education, 2017)
As the field of education has become a highly internationalised policy field in the last decade, international organisations such as the OECD play an ever more decisive role in the dissemination of knowledge, monitoring of outcomes, and research in education policy. Although the OECD lacks any binding governance instruments to put coercion on States or to provide material incentive, it has successively expanded its competences in this field. OECD advanced its status as an expert organisation in the field of education mainly by designing and conducting the international comparative PISA study. With PISA, the OECD was able to greatly influence national education systems. Basically, States were faced with external advice based on sound empirical data that challenged existing domestic policies, politics, and ideas. One prominent case for the impact of PISA is Germany. PISA was a decisive watershed in German education policy-making. Almost instantly after the PISA results were publicised in late 2001, a comprehensive education reform agenda was put forward in Germany. The experienced reform dynamic was highly surprising because the traditional German education system and politics were characterised by deep-rooted historical legacies, many involved stakeholders at different levels, and reform-hampering institutions. Hence, a backlog of grand education reforms have prevailed in Germany since the 1970s. The external pressure exerted by PISA completely changed that situation.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ejed.12220
Keywords: Germany; OECD; PISA; education policy; evidence-based policymaking; international large scale assessments